Widely rhythmic transcriptome in Calanus finmarchicus during the high Arctic summer solstice period - Payton, Laura; Hüppe, Lukas; Noirot, Celine; Hoede, Claire; Last, Kim; Wilcockson, David; Ershova, Elizaveta; Valière, Sophie; Meyer, Bettina (iScience, 2020)
Solar light/dark cycles and seasonal photoperiods underpin daily and annual rhythms of life on Earth. Yet, the Arctic is characterized by several months of permanent illumination (“midnight sun”). To determine the persistence of 24h rhythms during the midnight sun, we investigated transcriptomic dynamics in the copepod Calanus finmarchicus during the summer solstice period in the Arctic, with the lowest diel oscillation and the highest altitude of the sun's position. Here we reveal that in these extreme photic conditions, a widely rhythmic daily transcriptome exists, showing that very weak solar cues are sufficient to entrain organisms. Furthermore, at extremely high latitudes and under sea-ice, gene oscillations become re-organized to include <24h rhythms. Environmental synchronization may therefore be modulated to include non-photic signals (i.e. tidal cycles). The ability of zooplankton to be synchronized by extremely weak diel and potentially tidal cycles, may confer an adaptive temporal reorganization of biological processes at high latitudes.